2005
DOI: 10.1258/0049475053001949
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of head and neck cancers in Ilorin, Nigeria

Abstract: Eighty-nine cases of head and neck cancers were studied over a 5-year period (1997--2001) at the University of Ilorin Teaching Hospital, Nigeria. The most common cancer affecting the head and neck region was carcinoma which constituted 70.8% of all the cases studied. It was followed by the lymphomas and blastomas which accounted for 20.2% and 9%, respectively. The nose/paranasal sinuses were the most common site of primary cancer (18%) followed by thyroid (12.4%), nasopharynx (11.3%) and larynx (4.5%). Other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 10 publications
9
46
1
Order By: Relevance
“…Study from Ilorin another middle belt region of Nigeria country indicated the nose and the paranasal sinuses are the most common site of primary lesion and peak incidence in the 5 th decades of life. 27 Squanmous cell carcinoma accounted for 63.5% of all carcinoma in this study followed by Adenocystic carcinoma 14.2%, Adenocarcinoma 5.2%, metastic carcinoma 3.7%.Generally speaking squamous cell carcinoma account for the largest carcinoma almost all over the world as mentioned earlier. However the percentage of squamous cell carcinoma seen in this report is so low compared to previous studies in this centre and other centers in the country such as Ibadan, Ilorin, Lagos, 3,5,6,7,8,14 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Study from Ilorin another middle belt region of Nigeria country indicated the nose and the paranasal sinuses are the most common site of primary lesion and peak incidence in the 5 th decades of life. 27 Squanmous cell carcinoma accounted for 63.5% of all carcinoma in this study followed by Adenocystic carcinoma 14.2%, Adenocarcinoma 5.2%, metastic carcinoma 3.7%.Generally speaking squamous cell carcinoma account for the largest carcinoma almost all over the world as mentioned earlier. However the percentage of squamous cell carcinoma seen in this report is so low compared to previous studies in this centre and other centers in the country such as Ibadan, Ilorin, Lagos, 3,5,6,7,8,14 .…”
Section: Discussionsupporting
confidence: 63%
“…For example the mean age was 62 years in America, Canada 60 years. India 57 years, Britain 63 years and Australia 60 years but higher than cases reported from Lagos 49 years, Ibadan 48 years and previously reported cases from the department 45 years 11,13,24 Site of distribution showed a different pattern from previous studies from the institution 25,26 and the other region of the country with the maxillary antrum having the highest 37, closely followed by the mandible 36, the palate 35, the maxilla 30, the lips 15,4,7,8,27 the tongue 11, this simply means over 60% of all the carcinoma are located within the middle third of the face especially the maxillary antrum and its related surfaces. Previous study in the unit though mainly on intra-oral and not oro-facial carcinoma indicated oral mucous membrane as the main site occurrence with 63% of all the carcinoma.…”
Section: Discussionmentioning
confidence: 73%
“…This falls within the range of 1.1 to 2.3:1 found in most studies around the country. 14,16,22,24,25 The mean age of presentation for head and Neck lesions in this study was 32.7 years (33years for males and 32 years for females). This is lower than most studies conducted around the world.…”
Section: Discussionmentioning
confidence: 75%
“…Generally, head and neck cancers constitute between 5 and 50 % of all cancers globally, while in Nigeria, prevalence ranging from 20 to 44 cases per year has been reported in several centres [1][2][3][4][5]. While tobacco and alcohol are independent risk factors and etiologies for this condition, the immune system plays a significant role in the development.…”
Section: Introductionmentioning
confidence: 99%